Normal MRI findings of the knee in patients with clinically active juvenile idiopathic arthritis. Issue 102 (May 2018) - van Gulik, E. Charlotte; Hemke, Robert; Welsink-Karssies, Mendy M.; Schonenberg-Meinema, Dieneke; Dolman, Koert M.; Barendregt, Anouk M.; Nusman, Charlotte M.; Maas, Mario; Kuijpers, Taco W.; van den Berg, J. Merlijn
Highlights: Patients with clinically active JIA underwent MRI and were assessed using JAMRIS. In 35% of the clinically active JIA patients, MRI showed no signs of synovitis. In older children with clinically active JIA, MRI was more often found negative. Monitoring of disease activity with the use of MRI may prevent overtreatment. Abstract: Objective: In a number of patients with clinically active juvenile idiopathic arthritis (JIA), contrast-enhanced MRI shows no signs of synovitis. The objective of this study was to assess the frequency and the patient characteristics in clinically active JIA patients in which MRI showed no signs of synovitis. Methods: From our cohort of 313 patients in which contrast-enhanced MRI of the knee had been performed, we selected 72 JIA patients with clinically active disease involving the target joint. The validated Juvenile Arthritis MRI Scoring (JAMRIS) system was used to evaluate synovial thickening. Patients were divided into two groups based on MRI outcome: Group 1: thickened synovium on MRI (JAMRIS score ≥1) or Group 2: normal synovium on MRI (JAMRIS score 0). Patient characteristics and disease activity parameters were then compared. Results: In 35% (25/72) of these patients, MRI results contrasted with the clinical assessment (Group 2). In comparison to Group 1, the patients with discrepant findings were significantly older at the date of examination and JIA had been diagnosed at later age (median age of 13.2 vs. 10.9 and median age 10.0 vs. 8.0 respectively). In Group 2 there were significantly more patients with RF-negative polyarticular disease. Conclusion: Patients with RF-negative polyarticular JIA who had been diagnosed at a later age and were older at the time of MRI were most likely to be considered clinically active while MRI showed no signs of synovitis. These particular JIA patients may benefit from monitoring of disease activity by MRI to prevent overtreatment.